Stress Intensity Factor Equations for the Evolution of Surface and Corner Cracks to Through Cracks - Antonio Miranda; Rafael Marques; Marco Antonio Meggiolaro; Jaime Tupiassú Pinho de Castro (Fracture and Structural Integrity)
Part-through surface or corner 2D cracks are commonly found in structural components, even because practically all fatigue cracks tend to start this way. It is a reasonable hypothesis to model them assuming the shape of their fronts is approximately an elliptic arc, as supported by many fractographic observations. But their transition to a 1D through-crack, an important issue in many practical applications, is normally not properly addressed in fatigue life predictions. Although experimental results reveal that the frontier of surface cracks essentially retain their elliptical shape as they gradually grow into a through-crack, it is usual to assume they are immediately transformed into a through-crack when their depth reaches the cracked component thickness. This crude approximation may create a large jump in stress intensity values, leading to excessively conservative fatigue crack growth predictions, or else the crude shape jump hypothesis may induce false overload events that can much affect fatigue crack growth retardation models, leading to inadmissible non-conservative life predictions. To minimize such problems, an improved model to describe the transition of 2D surface cracks to 1D through-cracks is proposed and verified by crack propagation tests in two different materials, 4340 steel and polycarbonate (PC). Moreover, fatigue life predictions based on this improved model are compared with experimental results.